A educação das pessoas privadas de liberdade: o hiato entre a letra da lei e a realidade prisional - Gargioni, Danieli (2022)
Despite having a considerable framework of norms regulating education in the Brazilian prison system, with the formal purpose of reintegrating the inmates into society, contradictorily, the prison system, especially since the 1990s, has been growing alarmingly and the recidivism reaches very high numbers, according the most recently research. On the other hand, according to data from December 2019 (BRASIL, 2019a), only 16.53% of those incarcerated were in some educational activity. Given this terrifying scenario, the general objective of this dissertation is to verify whether the federal and Paraná rules on education in the prison system are effective or fulfill a role of maintenance of capitalist society, having as a time frame for this analysis the years 1984 to 2019. To achieve this purpose, a bibliographic research of primary and secondary sources was carried out, using the dialectical method, with the aid of content analysis. As for the primary sources, official norms and data on prison education were researched so that the gap between formal and substantial law could be checked. In relation to secondary sources, they anchored the analysis of this gap, enabling the understanding of the real intentions of the normative body. To achieve the main objective, a study was carried out on the development of the prison sentence and its relationship with the socioeconomic needs of each period. The concept of resocialization and emancipation was also researched, aiming to understand their differences and shed light on the possibility of an emancipatory education. Then, a study was undertaken on the right to education of inmates and their specificities. Through content analysis, we searched for norms related to prison education. Finally, the study of the normative body referring to prison education was related to official data from 2019 at the federal and Paraná level, on education in the penitentiary system, articulating them with secondary sources. As a result, it is concluded that the norms on education in the prison system are not fully implemented and, as a result, they end up being an effective tool to legitimize the segregationist punitive model of the penal system and to collaborate for the maintenance of class society.